2021
DOI: 10.1177/17588359211030210
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of eribulin in heavily pretreated patients with metastatic breast cancer in China: a multicenter retrospective study

Abstract: Background: Eribulin is a nontaxane microtubule inhibitor approved in China for patients with advanced breast cancer who show progression after ⩾2 lines of chemotherapy. The aim of this study was to determine the efficacy and safety profile of eribulin and explore potential predictive factors for the efficacy of eribulin among Chinese women with metastatic breast cancer (MBC) in real-world practice. Patients and Methods: A total of 272 consecutive MBC patients who were treated with eribulin between November 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
3
8
0
3
Order By: Relevance
“…The results of the prognostic analyses in the study were largely unchanged after exclusion of these individuals (data not shown). Other trials based on real-world data including > 100 patients report a wider spread of results for PFS (3.3-6.1 months) and OS (10.6-31.8 months) [7][8][9][10][11][12][13][14]. Differences in PFS could result from less frequent imaging or patient and tumour variability as well as differences in previous lines of MBC treatment between the cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the prognostic analyses in the study were largely unchanged after exclusion of these individuals (data not shown). Other trials based on real-world data including > 100 patients report a wider spread of results for PFS (3.3-6.1 months) and OS (10.6-31.8 months) [7][8][9][10][11][12][13][14]. Differences in PFS could result from less frequent imaging or patient and tumour variability as well as differences in previous lines of MBC treatment between the cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events for chemotherapy regimens were applicable to the National Cancer Institute Common Toxicity Criteria 5.0, which could be applied to grades 1 to 5 according to severity. [15]…”
Section: Methodsmentioning
confidence: 99%
“…Медиана числа предшествующих линий химиотерапии по поводу распространенной стадии достигла 5; эрибулин назначался в качестве 3-й линии всего у 13,1 % больных, в качестве 4-й линии -у 19,3 %, в качестве 5-й и более поздних линий терапиив 60,4 % случаев. Медиана числа проведенных циклов терапии эрибулином составила 4 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Медиана ОВ достигла 12,6 мес при назначении эрибулина в 3-й линии, 11,5 мес -в 4-й линии, и составила 9,7 мес при назначении в 5-й и более поздних линиях лечения.…”
Section: эффективность эрибулина в поздних линиях лечения мрмж: результаты реальной клинической практикиunclassified
“…В 2021 г. были представлены результаты крупного мультицентрового ретроспективного исследования, в котором 272 пациента получали химиотерапию эрибулином с ноября 2019 г. по октябрь 2020 г. в 9 институтах Китая [16]. Медиана числа предшествующих эрибулину линий химиотерапии составила 4 (2-5); 94,9 % больных получали ранее таксаны, 82,7 % -антрациклины.…”
Section: эффективность эрибулина в поздних линиях лечения мрмж: результаты реальной клинической практикиunclassified
See 1 more Smart Citation